The effect of genotype and the location of sampling on the mineral content of wool - Szigeti, Erika; Kátai, János; Komlósi, István; Oláh, János; Szabó, Csaba (Acta Agraria Debreceniensis, 2016)
Mineral supplementation is very important in high producing farm animals. The estimation of exact mineral intake is very difficult in forage eating animals, like sheep. Accessing of long term mineral status seems to be possible using wool mineral analysis. However several factors can affect the results. Therefore, the aim of this study was to test the effect of breed and sampling location on the mineral content of sheep wool. 20 Dorper and 20 Tsigai sheep were chosen from the same farm. Samples were obtained from 3 locations (withers, side and quarter) and tested for 8 elements: Ca, Mg, Na, Co, Cu, P, S, Se , Zn. The samples were cleaned with ethyl alcohol from organic contamination, then after adding nitric acid were mineral analized using ultrasonic cleaning unit. The samples were analysed with ICP-OES (Perkin-Elmer, Optima 3300 DV). Statistical analyses were carried out by GLM procedure of SAS statistical analyses software. Differences between means were checked with Tukey-test. Significant breed differences were detected in the case of Mg, Na, S, Se in spite of the same feeding regime. The wool mineral content were within the reference range. The sampling location had no effect on the mineral content of wool.